2022
DOI: 10.3390/antiox11020363
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Waste Products of Mangifera indica L. Reduce Adipogenesis and Exert Antioxidant Effects on 3T3-L1 Cells

Abstract: Several studies highlighted the beneficial value of natural compounds in the prevention and treatment of obesity. Here, we investigated the anti-obesity effects of extracts of peel and seed of mango (Mangifera indica L.) cultivated in Sicily (Italy) in 3T3-L1 cells. Mango Peel (MPE) and Mango Seed (MSE) extracts at a 100 µg/mL concentration significantly reduced lipid accumulation and triacylglycerol contents during 3T3-L1 adipocyte differentiation without toxicity. HPLC-ESI-MS analysis showed that both the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 78 publications
2
18
0
Order By: Relevance
“…The present study aimed at investigating whether peel and seed extracts of mango were capable of reducing lipotoxicity exerted by high doses of PA on differentiated 3T3-L1 adipocytes. The compositions of both MPE and MSE have been previously characterized by HPLC-ESI-MS analysis [ 35 , 43 ]. Data showed that both the extracts are rich in polyphenols with antioxidant properties [ 35 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study aimed at investigating whether peel and seed extracts of mango were capable of reducing lipotoxicity exerted by high doses of PA on differentiated 3T3-L1 adipocytes. The compositions of both MPE and MSE have been previously characterized by HPLC-ESI-MS analysis [ 35 , 43 ]. Data showed that both the extracts are rich in polyphenols with antioxidant properties [ 35 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The edible part of mango is only the pulp. However, it has been reported that mango peel and seed, which are the main bio-wastes of mango processing, contain high levels of bioactive compounds [ 42 , 43 ]. We previously demonstrated that extracts of mango peel and seed cultivated in Sicily exert anti-adipogenic effects by reducing the differentiation of 3T3-L1 fibroblasts into adipocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pictures were obtained using a Leica DM-IRB microscope and images were acquired at the magnification of 400×. The percentage of the positive area/field at ORO staining was quantified using ImageJ as indicated, as described by Pratelli et al [ 43 ]. To quantify the level of Oil Red O content, 100% isopropanol was added to each well before shaking at room temperature for 5 min, and the isopropanol-extracted sample was then measured at 490 nm with a microplate reader (OPSYS MR, Dynex Technologies, Chantilly, VA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The fruits, leaves, and roots of several plants contain bioactive compounds capable of exerting anti-oxidant, anti-inflammatory, and anti-cancer effects [ 10 , 11 , 12 , 13 , 14 ]. Recently, most of these compounds have also been shown to exert anti-obesity effects [ 15 , 16 , 17 ].…”
mentioning
confidence: 99%